Desenvolvimento de vacinas recombinantes e de teste de diagnóstico para controle da linfadenite caseosa - Rezende, Andréa de Fátima Silva (2013)
The caseous lymphadenitis (CLA) is a disease that affects mainly small ruminants and is caused by the bacteria Corynebacterium pseudotuberculosis. In Brazil the clinical prevalence CLA is 30%. The control measures are vaccination and diagnosis of infected animals. Currently, commercial vaccines are not completely effective, the same occur with the methods of diagnosis, because the medical signs are not immediately detectable. By sequencing and additional proteomic analysis, several targets were identified, including cp1002_0369 gene, which codifies a secreted protein which is probably described as a potentially antigenic phosphoesterase, that can subsequently be used in the development of recombinant vaccines and development of diagnostic tests. This protein was used as recombinant and it was tested as subunit vaccine and as a DNA vaccine and also to develop a diagnostic test based on ELISA. For this, the cp1002_0369 gene was cloned in the eukaryotic expression vector pTARGET and in a vector of expression in prokaryotes pAE. The recombinant protein CP0369 was purified and evaluated as a recombinant vaccine associated with both of the adjuvants xanthan and aluminum hydroxide and then measured in an indirect ELISA with sheep serum. The immunoprotective potential was assessed in a murine model by challenge with 104 CFU of strain Mic-6 of C. pseudotuberculosis in 9 vaccinal groups. The vaccine formulation that increased the survival rate of animals after challenge was the group containing the recombinant protein (rCP0369 + aluminum hydroxide). The ELISA for diagnostic of CL was evaluated by ROC analysis of 182 sera and showed a sensitivity and specificity of 90% and 75.6%, respectively. The format of ELISA assay (ELISA-rCP0369) can be used in the diagnosis of LC sheep herds with a good sensitivity index. However, new vaccine strategies employing the CP0369 protein will be evaluated to improve the effectiveness of the vaccine.